Hermenuticals of Human Movement and Sport: Holism and Harmony - Jirásek Ivo; Hurych Emanuel; Oborný Josef (Sciendo, 2018)
The paper deals with the hermeneutical approach to active human movement and sport. This topic has been more frequently examined in literature since 2010. This paper focuses on holism and harmony within the hermeneutics of sport. Some specific holistic approaches based on different viewpoints are described here. The key task of the middle part of the paper is to question and search for authentic meanings in sport. In this context, the theory of kinestructs and kinascepts by Eleaonor Metheny is briefly explained. The final part of the paper attempts to summarize possibilities for uncovering a deeper sense of human movement in the context of holism.